# Multiply Binomials When Coefficient is NOT One

## Multiply Binomials When Coefficient is NOT One - How it Works - Video

### Example 1

Example 1:

When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.

For F we multiply the 2x and x => x2.

For O we multiply the 2x and 5 => 10x.

For I we multiply the 1 and x => 1x.

For L we multiply the 1 and 5 => 5.

Now we have 2x2 + 10x + 1x + 5. Let's combine any like times and in this case we have 10x + 1x => 11x.

So our final answer is 2x2 + 11x + 5.

### Example 2

Example 2:

When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.

For F we multiply the 3x2 and 5x => 15x3.

For O we multiply the 3x2 and 6 => 18x2.

For I we multiply the -4 and 5x => -20x.

For L we multiply the -4 and 6 => -24.

Now we have 15x3 + 18x2 - 20x - 24. We don't have any like terms.

So our final answer is 15x3 + 18x2 - 20x - 24.

### Example 3

Example 3:

When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.

For F we multiply the 2xy2 and 4y => 8xy3.

For O we multiply the 2xy2 and -5 => -10xy2.

For I we multiply the 3 and 4y => 12y.

For L we multiply the 3 and -5 => -15.

Now we have 8xy3 - 10xy2 + 12y - 15. We don't have any like terms.

So our final answer is 8xy3 - 10xy2 + 12y - 15,